2021
DOI: 10.1016/j.bja.2021.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective ketamine effect on cardiac output: a population pharmacokinetic/pharmacodynamic modelling study in healthy volunteers

Abstract: Background: Ketamine has cardiac excitatory side-effects. Currently, data on the effects of ketamine and metabolite concentrations on cardiac output are scarce. We therefore developed a pharmacodynamic model derived from data from a randomised clinical trial. The current study is part of a larger clinical study evaluating the potential mitigating effect of sodium nitroprusside on the psychedelic effects of ketamine. Methods: Twenty healthy male subjects received escalating esketamine and racemic ketamine doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 20 publications
1
30
2
Order By: Relevance
“…There are two possible reasons why increasing doses of SK with propofol are less likely to produce hypotension: (i) due to the decrease in the TCI concentration of propofol, the dose-dependent depression of propofol on the circulation was alleviated; or (ii) the sympathomimetic properties of esketamine may, at least partially, counter propofol-induced haemodynamic depression. 37,38 It is reported that esketamine nasal spray could cause transient and asymptomatic blood pressure elevations. 37 Kamp et al 38 demonstrated that S-Ketamine increased cardiac output in a dose-dependent manner: 1.68 nmol/mL of the S-ketamine plasma concentration could cause a 25% increase in cardiac output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two possible reasons why increasing doses of SK with propofol are less likely to produce hypotension: (i) due to the decrease in the TCI concentration of propofol, the dose-dependent depression of propofol on the circulation was alleviated; or (ii) the sympathomimetic properties of esketamine may, at least partially, counter propofol-induced haemodynamic depression. 37,38 It is reported that esketamine nasal spray could cause transient and asymptomatic blood pressure elevations. 37 Kamp et al 38 demonstrated that S-Ketamine increased cardiac output in a dose-dependent manner: 1.68 nmol/mL of the S-ketamine plasma concentration could cause a 25% increase in cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 It is reported that esketamine nasal spray could cause transient and asymptomatic blood pressure elevations. 37 Kamp et al 38 demonstrated that S-Ketamine increased cardiac output in a dose-dependent manner: 1.68 nmol/mL of the S-ketamine plasma concentration could cause a 25% increase in cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…The data used in this analysis are part of a larger data set that was used previously to study the effects of sodium nitroprusside on ketamine-induced adverse effects, 9 and to construct a population pharmacokinetic model of ketamine and its metabolites, 10 as well as a pharmacodynamic model of ketamine-induced changes in cardiac output. 11 In the secondary analysis that is currently planned, we developed a population pharmacokinetic–pharmacodynamic model of ketamine and its metabolite norketamine to describe the relationship between plasma concentrations of S - and R -ketamine (and their metabolites) and pressure pain threshold and the change in external perception as a measure of ketamine psychotropic effect. The study protocol was approved by the Institutional Review Board (Medical Ethics Review Committee Leiden, Den Haag, Delft, Leiden University Medical Center, Leiden, The Netherlands) and registered at the trial register of the Dutch Cochrane Center (www.trialregister.nl) under registration No.…”
Section: Methodsmentioning
confidence: 99%
“…Ketamine can be converted to an active metabolite, norketamine, by CYP3A4 ( 27 ). Norketamine, included Nor-S-ketamine and Nor-R-ketamine can retain anesthetic effects, which can explain the maintenance of the anesthesia at lower blood ketamine concentrations ( 30 , 31 ). Norketamine can also cross the blood–brain barrier and induces psychoactive effects ( 23 , 32 ).…”
Section: Discussionmentioning
confidence: 99%